2009
DOI: 10.25182/jgp.2009.4.2.109-115
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Jalur Faktor-Faktor Yang Mempengaruhi Ketahanan Pangan Rumah Tangga Di Kabupaten Lebak, Propinsi Banten

Abstract: <p class="MsoTitle" style="margin: 0cm 13.05pt 6pt 17.85pt; text-align: justify; text-indent: 26.95pt;"><span style="font-size: 10pt;" lang="en-us" xml:lang="en-us">The objective of the study was to analyze direct and indirect factors that influence household’s food security. The study design was a crosectional study.  Research was conducted in </span><span style="font-size: 10pt;" lang="en-us" xml:lang="en-us">Pasindangan and Banjarsari Village, Cileles and Warunggunung Subdistrict, Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 0 publications
1
5
0
11
Order By: Relevance
“…Looking at the data regarding ten-highest high-iron foods consumed, the two-most frequent iron consumed foods came from plants sources, which was tempeh and tofu. One study highlighted that there was a link between land ownership and house-hold food security (Tanziha & Herdiana, 2009). Therefore, because of living in rural region, plants sources, which are easy to access and free, become the most frequent consumed of iron foods to fulfi ll the iron requirement.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking at the data regarding ten-highest high-iron foods consumed, the two-most frequent iron consumed foods came from plants sources, which was tempeh and tofu. One study highlighted that there was a link between land ownership and house-hold food security (Tanziha & Herdiana, 2009). Therefore, because of living in rural region, plants sources, which are easy to access and free, become the most frequent consumed of iron foods to fulfi ll the iron requirement.…”
Section: Resultsmentioning
confidence: 99%
“…It is possibility due to the location of the study, which was in rural region, which mostly still have larger land for farming. In Lebak, a study found that there was a positive correlation between land ownership and house-hold food security (Tanziha & Herdiana, 2009). This implies that the more land they owned, the greater the chance of achieving household food security.…”
Section: Resultsmentioning
confidence: 99%
“…Penelitian mengenai analisis jalur pernah dilakukan oleh Tanzia, Ike dan Herdiana (2009) dengan judul Analisis Jalur Faktor-Faktor Yang Mempengaruhi Ketahanan Pangan Rumah Tangga di Kabupaten Lebak Provinsi Banten. Kesimpulan dari hasil penelitian tersebut adalah tidak terdapat hubungan yang signifikan antara pendidikan kepala rumah tangga, pendidikan irt, pengetahuan gizi ibu dan dukungan sosial dengan ketahanan pangan rumah tangga.…”
Section: Pendahuluanunclassified
“…Hal ini sejalan dengan karakteristik rumah tangga berdasarkan tingkat ketahanan pangan rumah tangga berdasarkan metode HFIAS bahwa dalam penelitian ini ukuran rumah tangga diduga memengaruhi tingkat ketahanan pangan. Hal ini juga didukung oleh penelitian Mustisya et al yang menyatakan bahwa terdapat hubungan yang signifikan antara ukuran rumah tangga dengan tingkat ketahanan pangan rumah tangga (18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Hasil Perbedaan Karakteristik Sosial Ekonomi Berdasarkan Tinunclassified
“…Pendidikan orang tua dalam hal ini yaitu lama sekolah kepala rumah tangga dan ibu rumah tangga tidak memiliki perbedaan antara kelompok rumah tangga tahan pangan dan tidak tahan pangan baik yang diukur dengan metode HFIAS maupun metode Maxwell yang dimodifikasi. Hal ini sejalan dengan penelitian yang dilakukan oleh Tanziha dan Haerdiana bahwa tidak terdapat hubungan yang signifikan antara pendidikan kepala rumah tangga dengan tingkat ketahanan pangan rumah tangga, begitu pula pendidikan ibu rumah tangga, tidak berhubungan secara signifikan dengan tingkat ketahanan pangan rumah tangga (25). Hal ini sejalan dengan dengan penelitian Kartika dan Ririn bahwa tidak terdapat hubungan yang signifikan antara pendidikan kepala rumah tangga dengan tingkat ketahanan pangan rumah tangga, begitu pula pendidikan ibu rumah tangga (7).…”
Section: Hasil Perbedaan Karakteristik Sosial Ekonomi Berdasarkan Tinunclassified